Incorporation of Brazilian Diatomite in the Synthesis of An MFI Zeolite - Vinaches, Paloma (2019)
The need for greener procedures is a fact to reduce residues, to decrease industrial costs, and to accomplish the environmental agreements. In an attempt to address this question, we propose the addition of a natural resource, Brazilian diatomite, to an MFI zeolite traditional synthesis. We have characterized the resulting product with different techniques, such as X-ray diffraction, microscopy, and gas sorption, and, afterwards, we evaluate the greenness of the process by the Green Star method. The results were promising: We obtained the desired topology in the form of small crystallites aggregated and a pore diameter of 0.8 nm. In conclusion, the product has the necessary characteristics for an adsorption or catalytic future tests and escalation to industrial production.